Field pea can replace soybean meal-corn mixtures in the fattening concentrate of young bulls improving the digestibility. (5th December 2022) - Lobón, S.; Joy, M.; Casasús, I.; Blanco, M.
Abstract: The inclusion of pea ( Pisum sativum ) in the fattening concentrate at 0%, 15%, 30%, and 45% as a replacement for soybean meal and corn was evaluated on in vitro and in vivo digestibility studies of young Parda de Montaña bulls. In the in vitro trial, gas production was determined with an Ankom system for 48 h. The 30%pea and 45%pea concentrates increased the organic matter (OM) degradability, the ammonia-N content and the ratio of acetic:propionic, with no effect on gas production, final ruminal pH and total volatile fatty acid production. In the in vivo assay, 4 young bulls (initial weight 251 ± 4 kg) received restricted amounts of concentrates plus straw during 4 consecutive experimental periods. No differences in intake were observed and 30%pea and 45%pea had higher digestibility of crude protein (CP), and OM than the rest of treatments. The nitrogen intake increased linearly with the inclusion of pea with similar nitrogen urinary and faecal excretions, and the nitrogen retained was greater in 30%pea and 45%pea than the rest of treatments. The plasma concentrations of IGF-1, total protein, β-hydroxybutyrate and urea at the beginning and at the end of each period were not affected by the inclusion of pea. In conclusion, the total replacement of soybean-corn mixtures by pea in the fattening concentrate of bulls could be recommended as it improved the CP digestibility and nitrogen retention. Highlights: Feeding pulses to livestock is encouraged to reduce the dependency on soybean. Proportions of pea in the fattening concentrate of young bulls were evaluated. The digestibility and retained nitrogen increased with pea inclusion. Pea can totally replace soybean in beef fattening concentrates.